PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP INDEKS SAHAM SYARIAH INDONESIA ( ISSI ) DI BURSA EFEK INDONESIA TAHUN 2015 - 2019 - As'ari, Erham; Marfudin, Marfudin; Arifin, Nandang Syamsul; Supadi, Supadi (Sekolah Tinggi Ekonomi Dan Bisnis Islam Darussalam, 2021)
Influence of Inflation and the exchange Rate of the Rupiah on the Indonesia Sharia (ISSI) stock index in the indonesia stock exchange (BEI) in 2015 - 2019. This research is a quantitative study using secondary data collection methods, the data obtained is then processed using the Eviews tool version 11. Analytical techniques used were linear regression, while hypothesis test used t - test and F test with significance level of 5%. The classical assumptions test used in this study include normality, multicollinearity, heteroscedasticity and autocorrelation test. The results of this study that T-test shows that the influence of inflation variable, partially positive effect is not significant to the Indonesian Islamic stock index (ISSI), while the influence of the rupiah exchange rate variable (exchange rate), has a non-significant negative effect on the Islamic stock index Indonesia (ISSI). The F test shows that the influence of inflation variables and the exchange rate of the rupiah (exchange rate) simultaneously have a significant effect on the Indonesian Islamic stock index (ISSI).